OP0072 Inhibition of Notch1 Promotes Hedgehog Signaling in A HES1-Dependent Manner and Exacerbates Experimental Osteoarthritis. (15th July 2016) - Lin, N.Y.; Distler, A.; Beyer, C.; Philipi-Schöbinger, A.; Stock, M.; Niemeier, A.; Dell'Accio, F.; Schett, G.; Distler, J.H.
Abstract : Background: The Notch pathway is one of the so-called morphogen pathways, which are evolutionary conserved key-regulators of embryonic development. Notch signaling has recently been implicated in the pathogenesis of osteoarthritis (OA). However, cell-type and context dependent differences in outcome have been reported and the underlying molecular mechanisms are incompletely understood. Objectives: OA is characterized by degeneration of articular cartilage, limited intraarticular inflammation with synovitis, changes in periarticular and subchondral bone and osteophyte formation by endochondral ossification. Several studies have identified Notch- and Hedgehog-signaling as essential pathways involved in cartilage development and bone remodeling. Methods: Notch and hedgehog signaling were analyzed by real-time PCR and immunohistochemistry. Mice overexpressing a Notch-1 antisense construct (Notch-1 AS) were employed as a model of impaired Notch signaling. Experimental OA was induced by destabilization of the medial meniscus (DMM). The extent of cartilage destruction and osteophyte formation was analyzed by safranin-O staining with subsequent assessment of the OARSI and Mankin scores and μCT scanning. Collagen X staining was used as a marker of chondrocyte hypertrophy. The role of Hes-1 was investigated with knockdown and overexpression experiments. Results: Notch signaling was activated in human and murine OA with increased expression of Jagged1, Notch-1, accumulation of the Notch intracellular domain (NICD1) and increased transcription of Hes-1. Notch1 AS mice showed exacerbated osteoarthritis with increases in OARSI scores, osteophyte formation, increased subchondral bone plate density, collagen X and osteocalcin expression and elevated levels of Epas1 and ADAM-TS5 mRNA. Inhibition of the Notch pathway induced activation of hedgehog signaling with induction of Gli-1 and Gli-2 and increased transcription of hedgehog target genes. The regulatory effects of Notch signaling on Gli-expression were mimicked by Hes-1. Conclusions: Inhibition of Notch signaling activates hedgehog signaling, enhances chondrocyte hypertrophy and exacerbates experimental osteoarthritis including osteophyte formation. These data suggest that the activation of the Notch pathway may serve to limit aberrant hedgehog signaling in OA. Disclosure of Interest: None declared